Dietary intakes of branch chained amino acids and obesity risk among Chinese gestational diabetes women - Yang, Xiaoyun; Li, Weiqin; Li, Wei; Liu, Huikun; Wang, Leishen; Leng, Junhong; Fan, Yuxin; Yang, Xilin; Liu, Ming; Hu, Gang (Frontiers in Nutrition, 2024)
Introduction: Epidemiological studies have assessed the correlation between daily dietary branch chain amino acid (BCAA) intakes and the risk of obesity, however, the findings from these studies were inconsistent and investigations among GDM women were few.Objective: The present study was to investigate the associations of daily BCAA intakes with the risks of overweight and abdominal obesity among women with prior gestational diabetes mellitus (GDM) postpartum.We performed a cross-sectional study of 1263 women with prior GDM at 1-5 years post-delivery. Logistic regression models were used to estimate the associations of daily dietary intakes of BCAAs with the risks of overweight and abdominal obesity.The multivariable-adjusted odds ratios (ORs) across quartiles of daily BCAA intakes postpartum were 1.42 (95% confidence interval [CI] 1.02-1.97), 1.00 (reference), 1.21 (95% CI 0.88-1.68), and 1.31 (95% CI 0.95-1.81) for general overweight, and 1.38 (95% CI 0.99-1.90), 1.00, 1.19 (95% CI 0.86-1.64), and 1.43 (95% CI 1.04-1.98) for abdominal obesity, respectively. Women with the lowest quartile of daily BCAA intakes significantly increased the risks of general overweight (OR 1.49; 95 %CI 1.06-2.09) and abdominal obesity (OR 1.50; 95 %CI 1.08-2.11) compared with women at quartile 2 of daily BCAA intakes after further adjustment of daily energy intake.The present study indicated that daily lower BCAA intakes were associated with increased risks of general overweight and abdominal obesity among women with prior GDM.